2017
DOI: 10.1002/ppul.23737
|View full text |Cite
|
Sign up to set email alerts
|

Medical mishap as a cause of non‐resolving pneumonia

Abstract: A 15-year old boy was referred for evaluation of fever, productive cough, and recurrent/persistent right lower lobe (RLL) pneumonia of 1-month duration. Chest computed tomography scan showed RLL consolidation, with minimal pleural effusion and a liver abscess with sharp borders, containing a solid calcification in the lower portion. History revealed acute appendicitis with laparoscopic appendectomy 6 months prior to presentation, during which a fecalith dropped to the peritoneal cavity. Following laparoscopica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, complications of a retained appendicolith are serious and include intra-abdominal abscess, perihepatic abscess, and delayed wound healing through fistula formation [ 1 , 6 ]. There are even rarer complications: Toukan et al reported a case of recurrent right lower lobe pneumonia associated with a liver abscess in a 15-year-old male secondary to retained appendicolith after appendectomy [ 8 ]. The time of symptom presentation in patients with appendicolith after appendectomy varies.…”
Section: Discussionmentioning
confidence: 99%
“…However, complications of a retained appendicolith are serious and include intra-abdominal abscess, perihepatic abscess, and delayed wound healing through fistula formation [ 1 , 6 ]. There are even rarer complications: Toukan et al reported a case of recurrent right lower lobe pneumonia associated with a liver abscess in a 15-year-old male secondary to retained appendicolith after appendectomy [ 8 ]. The time of symptom presentation in patients with appendicolith after appendectomy varies.…”
Section: Discussionmentioning
confidence: 99%